Kerjasama Indonesia-Australia Melalui World Mosquito Program Studi Kasus Pengendalian Demam Berdarah Dengue di Kota Bandung 2023–2024 - Akwal Waffi Kariswan; Achdijat Sulaeman (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines Indonesia–Australia cooperation through the World Mosquito Program in controlling dengue fever in Bandung City during 2023–2024 from a global health diplomacy perspective. Using a qualitative interpretative library research design grounded in constructivist epistemology, the study synthesizes peer-reviewed literature and institutional documents on Wolbachia technology, bilateral cooperation, and dengue governance. The findings demonstrate that the impact of the program cannot be reduced to short-term epidemiological outcomes, but reflects a gradual transformation in vector control paradigms shaped by policy coordination, institutional learning, and transnational knowledge transfer. The cooperation functions not only as a technological intervention but also as a diplomatic mechanism that enhances policy legitimacy, governance capacity, and trust among stakeholders. Variations in effectiveness highlight the importance of local context, political commitment, and adaptive evaluation frameworks. The study argues that sustainability depends on the integration of global standards into domestic institutions and the alignment of preventive health innovation with national policy priorities. This research contributes to global health diplomacy scholarship by illustrating how bilateral cooperation operationalizes biotechnology within complex governance environments and long-term public health strategies.